2021
DOI: 10.3390/foods10050972
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Device Assisted-Estimation of the Quality of Edible Oils with Repetitive Frying

Abstract: This study investigated chemosensory degradations of soybean and canola oils with repeated frying in order to estimate the quality of the oils. Methods: Chemical parameters including oxygen induction time, acid value, p-anisidine value, malondialdehyde, and total polar compounds were measured. Electronic nose and electronic tongue analyses were performed to assess sensory properties. Multivariate analyses were employed to investigate relationships among tastes and volatile compounds using principal component a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…The cooking, mainly frying, of oils plays an important role in flavor development. For instance, Lee et al [ 42 ] found that the frying of soybean and canola oils increased volatile concentration, and 2-heptenal, ethyl butyrate, and 2,4-pentanedione were the major volatiles in soybean oil, whereas ethyl butyrate and linalool were abundant in canola oil. Moreover, Xiao et al [ 43 ] stated that the content of volatile aldehydes and alcohols was developed at 120 °C, whereas ketones and furans were produced at 150 °C, and acids were formed at 180 °C during the heating of soybean oil.…”
Section: Effect Of Processing On the Flavor Compounds Of Edible Oilsmentioning
confidence: 99%
“…The cooking, mainly frying, of oils plays an important role in flavor development. For instance, Lee et al [ 42 ] found that the frying of soybean and canola oils increased volatile concentration, and 2-heptenal, ethyl butyrate, and 2,4-pentanedione were the major volatiles in soybean oil, whereas ethyl butyrate and linalool were abundant in canola oil. Moreover, Xiao et al [ 43 ] stated that the content of volatile aldehydes and alcohols was developed at 120 °C, whereas ketones and furans were produced at 150 °C, and acids were formed at 180 °C during the heating of soybean oil.…”
Section: Effect Of Processing On the Flavor Compounds Of Edible Oilsmentioning
confidence: 99%
“…The processing may combine with air or oxidation‐promoting substances in the feed (Winkler–Moser et al, 2020). In addition, heat treatment may open the double bonds of unsaturated fatty acids, and the more double bonds in the fatty acid chain, the greater chance of oxidation during heating (Lee et al, 2021). Lipid oxidation is one of the significant causes of deterioration in the quality of many foods, causing oils to develop a rancid odor (Cong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%